Development aid, openness to trade and economic growth in Least Developed Countries: bootstrap panel Granger causality analysis - TEKİN, RIFAT BARIŞ (ELSEVIER SCIENCE BV, 2012)
This study examines causal relations among development aid, openness to trade and economic growth in the Least Developed Countries (LDC), for the period between 1970 and 2010. The variables under scrutiny are real per capita GDP, openness to trade ratio and total net Official Development Assistance as share of national income. By making use of a new Granger causality testing approach properly taking into account cross-sectional dependence and heterogeneity issues, this paper finds no significant causality relation among foreign aid, openness to trade, and economic growth in a panel of African LDCs. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Arasli
Keywords: Economic growth; openness to trade; development aid; Least Developed Countries; Granger causality; POLICIES